Talk Shows and Leaflets Improve Senior High School Student Knowledge of Chronic Kidney Diseases - Laurensia Imelda; Rudi Supriyadi; Yenni Zuhairini (Althea Medical Journal, 2020)
Background: The increase of chronic kidney disease (CKD) incidence and its related costs in developing countries have urged all levels of society prevent this disease. Prevention can be effectively done when someone has good knowledge about the disease. This study aimed to observe the change in knowledge about CKD before and after education sessions in the form of talk shows as well as through the leaflet media among senior high school students.Methods: This was a cross-sectional observational quantitative study on 71 first-grade students participated in World Kidney Day 2019 event. The questionnaire was distributed before and after the education program and data collected were analyzed using the Wilcoxon-signed rank test and Mann-Whitney test to explore changes in the level of knowledge based on the characteristics of the subjects.Results: The median level of student knowledge before education was 76% (16-96%), which increased to 92% (28-100%) after education (p<0.001). No significant correlation was observed between knowledge about CKD and gender (p=0.486), family history of CKD (p=0.281), and health workers as parents (p=0.543).Conclusion: There is a significant improvement in knowledge of CKD before and after an education session through talk shows and leaflets among senior high school students. Health educations need to be regularly given to young adolescents using different approaches to increase their knowledge about various topics.